Home and school environmental factors as correlates of social adjustment of students with learning disabilities in Oyo state, Nigeria (2013)
The present study examined home and school environmental factors as correlates of social adjustment in a sample of one hundred and twenty secondary school students with learning disabilities. The multi-stage sampling procedure, purposive sampling as well as simple random sampling were adopted in the selection of study sample. The result of the study revealed home and school environments to be positively correlated with social adjustment thus, the coefficient of home environmental factors with social adjustment is .313; p= .000; the coefficient of school environmental factors with social adjustment is .402, p = .006; and the coefficient of peer interaction with sibling interaction is .288; p = .000. These findings indicated that factors in the home such as parenting styles, parents1 own past experiences as a child, stress within the family setting and sibling interactions as well as interpersonal relationships at school played significant roles in assisting students with learning disabilities in developing competency in social interactions. Both sibling and peer interaction were reported to be positively correlated with each other. As a result, both types of interpersonal relationships should be encouraged and enforced among students with learning disabilities. The study has implications for educationist sand parents as well.